2016
DOI: 10.1038/srep20823
|View full text |Cite
|
Sign up to set email alerts
|

PFR peptide, one of the antimicrobial peptides identified from the derivatives of lactoferrin, induces necrosis in leukemia cells

Abstract: LF11-322 (PFWRIRIRR-NH2) (PFR peptide), a nine amino acid-residue peptide fragment derived from human lactoferricin, possesses potent cytotoxicity against bacteria. We report here the discovery and characterization of its antitumor activity in leukemia cells. PFR peptide inhibited the proliferation of MEL and HL-60 leukemia cells by inducing cell death in the absence of the classical features of apoptosis, including chromatin condensation, Annexin V staining, Caspase activation and increase of abundance of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 54 publications
3
29
0
3
Order By: Relevance
“…Some examples are represented by the fragment 1-11 deriving from the reduction of lactoferricin H (GRRRSVQWCAV) with antiviral and high antibacterial activity (Bruni et al 2016;Wang et al 2016), which were confirmed in animal models and in a phase 1 study in human volunteers (Bruni et al 2016), and by a tetrameric peptide derived from lactoferricin B ((RRWQWR) 4 ) exhibiting specific cytotoxic effects against oral squamous-cell carcinoma cell lines (Solarte et al 2015). This antitumor activity was further confirmed by the PFR-peptide (Table 3) derived from lactoferricin H that induced necrotic cell death and G0/G1 cell cycle arrest in MEL and HL-60 leukemia cell lines (Lu et al 2016). In this study, researchers demonstrated that PFR-peptide inhibited leukemia cell growth in vivo in immune-compromised mice transplanted with MEL cells.…”
Section: Whey Proteins Deriving Cryptidessupporting
confidence: 54%
“…Some examples are represented by the fragment 1-11 deriving from the reduction of lactoferricin H (GRRRSVQWCAV) with antiviral and high antibacterial activity (Bruni et al 2016;Wang et al 2016), which were confirmed in animal models and in a phase 1 study in human volunteers (Bruni et al 2016), and by a tetrameric peptide derived from lactoferricin B ((RRWQWR) 4 ) exhibiting specific cytotoxic effects against oral squamous-cell carcinoma cell lines (Solarte et al 2015). This antitumor activity was further confirmed by the PFR-peptide (Table 3) derived from lactoferricin H that induced necrotic cell death and G0/G1 cell cycle arrest in MEL and HL-60 leukemia cell lines (Lu et al 2016). In this study, researchers demonstrated that PFR-peptide inhibited leukemia cell growth in vivo in immune-compromised mice transplanted with MEL cells.…”
Section: Whey Proteins Deriving Cryptidessupporting
confidence: 54%
“…From previous reports, the mechanism of the anti-cancer effects of AMPs against cancer cells includes multiple directions such as apoptosis, necrosis, and autophagy [3537]. We previously reported that FF/CAP18 induces apoptotic cell death in HCT116 cells through dynamic changes in the levels of metabolic profiles and revealed that the glycolytic pathway was restricted, resulting in reduced energy status [38].…”
Section: Discussionmentioning
confidence: 99%
“…Although AMPs are primarily known for their antimicrobial properties, some examples and their derivatives are reported as potent antitumor agents with low toxicity such as temporin-1CEa, ascaphin-8, alyteserin-2 and magainin-2 [13][14][15][16][17]. These AMPs bind to the plasma membrane and cause cell death by either necrosis or apoptosis [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%